(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: A high prevalence of complementary and alternative medicine (CAM) use has been documented in children with chronic illnesses. Conversely, evidence-based medicine is considered an important contributor in providing the best quality of care. METHODS: We performed a systematic overview/synthesis of all Cochrane reviews published between 1995 and 2012 in paediatrics that assessed the efficacy, and clinical implications and limitations of CAM use in children. Main outcome variables were: percentage of reviews that concluded that a certain intervention provides a benefit, percentage of reviews that concluded that a certain intervention should not be performed, and percentage of studies that concluded that the current level of evidence is inconclusive. RESULTS: A total of 135 reviews were included – most from the United Kingdom (29/135), Australia (24/135) and China (24/135). Only 5/135 (3.7%) reviews gave a recommendation in favour of a certain intervention; 26/135 (19.4%) issued a conditional positive recommendation, and 9/135 (6.6%) reviews concluded that certain interventions should not be performed. Ninety-five reviews (70.3%) were inconclusive. The proportion of inconclusive reviews increased during three, a priori-defined, time intervals (1995–2000: 15/27 [55.6%]; 2001–2006: 33/44 [75%]; and 2007–2012: 47/64 [73.4%]). The three most common criticisms of the quality of the studies included were: more research needed (82/135), low methodological quality (57/135) and small number of study participants (48/135). CONCLUSIONS: Given the disproportionate number of inconclusive reviews, there is an ongoing need for high quality research to assess the potential role of CAM in children. Unless the study of CAM is performed to the same science-based standards as conventional therapies, CAM therapies risk being perpetually marginalised by mainstream medicine.